2018
DOI: 10.1016/j.bja.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of dexmedetomidine, propofol, sevoflurane, and S-ketamine on regional cerebral glucose metabolism in humans: a positron emission tomography study

Abstract: NCT02624401.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 34 publications
0
41
1
Order By: Relevance
“…Our results appear at odds with a recent report (Schroeder et al, 2016), where mLOC occurred despite unchanged levels of overall activity during ketamine-induced dissociative anesthesia (Pender, 1971). But, whereas most first-line anesthetics decrease cerebral metabolism (Laaksonen et al, 2018;Pilge et al, 2014), ketamine differentially affects cerebral hemodynamics and neural firing with a net neutral effect (Cavazzuti et al, 1987;Laaksonen et al, 2018). Keeping in mind that functional brain imaging in the clinical setting relies on changes in cerebral metabolism as a proxy for neural firing (e.g., FDG-PET CT or BOLD signal in fMRI), it is not surprising that Schroeder et al (2016) found a preserved overall firing rate.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results appear at odds with a recent report (Schroeder et al, 2016), where mLOC occurred despite unchanged levels of overall activity during ketamine-induced dissociative anesthesia (Pender, 1971). But, whereas most first-line anesthetics decrease cerebral metabolism (Laaksonen et al, 2018;Pilge et al, 2014), ketamine differentially affects cerebral hemodynamics and neural firing with a net neutral effect (Cavazzuti et al, 1987;Laaksonen et al, 2018). Keeping in mind that functional brain imaging in the clinical setting relies on changes in cerebral metabolism as a proxy for neural firing (e.g., FDG-PET CT or BOLD signal in fMRI), it is not surprising that Schroeder et al (2016) found a preserved overall firing rate.…”
Section: Discussioncontrasting
confidence: 99%
“…Inter and intra-subject variabilities could be partly due to anesthesia injected to the animals. Indeed, the effects of different anesthetic drugs on glucose metabolism in the human brain have been recently reported [34] showing that propofol decreased glucose metabolism compared to saline placebo. In preclinics, studies using isoflurane anesthesia reported a higher glucose level post-scan compared to pre-scan in rats, suggesting a different impact of isoflurane on glycemia [22,35].…”
Section: Plos Onementioning
confidence: 99%
“…e performance of the anesthetic depth monitors was better when propofol was used. Very wide variation was found in the combination of AEP and sevoflurane [22,25,[31][32][33]. It seems the monitors are at best at giving the EC50, at which there is a 50% chance that the patient has reached the end point, and we have not yet found an anesthetic depth monitor that has high sensitivity and specificity and not affected by the anesthetic technique.…”
Section: Discussionmentioning
confidence: 87%